Catching the intangible: a role for emotion?. (2020) - Montefinese, Maria; Ambrosini, Ettore; Visalli, Antonino; Vinson, David
Abstract: A crucial aspect of Gilead and colleagues' ontology is the dichotomy between tangible and intangible representations, but the latter remains rather ill-defined. We propose a fundamental role for interoceptive experience and the statistical distribution of entities in language, especially for intangible representations, that we believe Gilead and colleagues' ontology needs to incorporate.